Iohexol-based assessment of intestinal permeability in broilers challenged with Eimeria maxima, Clostridium perfringens or both - Calik, Ali; Niraula, Abhisek; Dong, Bingqi; Blue, Candice E. C.; Fenster, Davis A.; Dalloul, Rami A. (Frontiers in Physiology, 2024)
Impaired intestinal integrity in broilers reduces performance and health, highlighting the importance of accurately measuring intestinal permeability (IP) to maintain gut health. The objective of this study was to evaluate the efficiency of iohexol as an IP marker in broilers challenged with Eimeria maxima, Clostridium perfringens, or both during both peak challenge (day [d] 21) and recovery (d 28) periods. One-day-old male Ross 708 birds (n = 56) were distributed into 4 treatment groups: NC (no-challenge control); EM (challenged with 5,000 E. maxima sporulated oocysts/bird on d 15); CP (challenged with 1.0 × 108 CFUs/bird of C. perfringens on d 19 and d 20); and EM + CP (challenged by co-infection of E. maxima and C. perfringens as described). On d 21 and d 28, each bird received an iohexol dose of 64.7 mg/kg body weight via oral gavage. One hour later, blood samples were collected from 14 birds (12 in EM) per group on d 21 and from 7 birds (6 in EM) on d 28. For lesion scoring and ileum collection, 7 birds per group (6 birds in EM) were sampled on each d 21 and d 28. Birds in the EM and EM + CP groups had lower body weight gain (BWG) compared to the NC and CP groups on d 19–21 (P ≤ 0.05). These birds also exhibited significantly greater lesion scores and markedly higher serum iohexol levels on d 21 (P ≤ 0.05). However, no significant differences in serum iohexol levels were observed among treatment groups following recovery on d 28. Moreover, significant differentials were observed in the mRNA abundance of key tight junction proteins (CLDN1, CLDN2, and ZO3), pro-inflammatory cytokines (IL-1β, IFNγ, and IL-22), and gut health markers (GLP2, OLFM4, and MUC2) in the EM and EM + CP groups compared to the NC and CP groups on d 21. In conclusion, this study demonstrates that iohexol is an effective marker for assessing IP in broilers under different enteric challenge conditions.